Aufklärung und Hofkultur in Dresden

[Art.] 651 ›Monumenta Paderbornensia‹ - Süßmann, Johannes (Credo. Christianisierung Europas im Mittelalter. Eine Ausstellung im Erzbischöflichen Diözesanmuseum, im Museum in der Kaiserpfalz und in der Städtischen Galerie Am Abdinghof zu Paderborn, 26. Juli bis 3. November 2013, Bd. 2: Katalog)

mm-Wave System-On-Chip Design in 0,13µm SiGe BiCMOS - Scheytt, Christoph; Sun, Yaoming; Schmalz, Klaus; Mao, Yanfei; Wang, Ruoyu; Debski, Wojciech; Winkler, Wolfgang (W 06 (EuMC & EuMIC))

Design and Analysis of Down-Conversion Gate/Base-Pumped Harmonic Mixers Using Novel Reduced-Size 180 ^° Hybrid With Different Input Frequencies - Kuo, Jhe-Jia; Lien, Chun-Hsien; Tsai, Zuo-Min; Lin, Kun-You; Schmalz, Klaus; Scheytt, Christoph; Wang, Huei (Microwave Theory and Techniques, IEEE Transactions on)
In this paper, a novel 180°hybrid with different input frequencies is proposed to combine RF and local oscillator (LO) signals with different frequencies in a gate/base-pumped harmonic mixer. The detailed analysis and design procedures are presented in this paper. To further reduce the chip size, the multilayer metallization above the lossy silicon substrate is employed to implement the hybrid. A V-band down-converted 2× harmonic mixer in 90-nm CMOS process and a D-band down-converted 4× harmonic mixer in the 130-nm SiGe process are designed, fabricated, and measured to verify the concept. The 2× harmonic mixer possesses 0-dB conversion gain at 60 GHz with 0-dBm LO power with merely 2.4-mW dc power. The 4× harmonic mixer achieves 0.5-dB conversion gain at 120 GHz with 2-dBm LO power and 27.3-mW dc power. With the proposed reduced-size 180° hybrid, gate/base-pumped harmonic mixers are very attractive in transceivers demanding low LO frequency and power.

Nano-/Mikroelektronik als Enabler für neue Ansätze - Scheytt, Christoph (HNI-Forum September)
50 Jahre Moore‘s Gesetz ? „More Moore“ & „More than Moore“ ? Miniatur-Radar-System ? Silizium-Photonik für schnelle Kommunikation ? Photonischer Winkelsensor

RF-MST Cluster Workshop on MEMSWAVE 2013 - Scheytt, Christoph (RF-MST Cluster Workshop on MEMSWAVE 2013)

Strategies for Energy-Efficient 100 Gb/s Baseband - Scheytt, Christoph; Kraemer, Rolf; Kallfass, Ingmar (W 19 (EuMC & EuMIC))

A 220-245 GHz Switched Beam Butler Matrix in 0,13µm SiGe BiCMOS technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (IEEE BIPOLAR / BiCMOS CIRCUITS AND TECHNOLOGY MEETING,)
This paper presents a 220-245 GHz 4 way Butler Matrix chip in 0.13μm SiGe BiCMOS technology. The chip features four 230 GHz amplifiers with almost 9 dB of gain. A SP4T switch is integrated to select between the four outputs of the beamforming network. Finally, an amplifier used to compensate the losses of the SP4T is integrated. The chip exhibits 0 dB of insertion gain and draws 104 mA from 3.3 V supply mainly consumed by the amplifiers. The entire chip occupies 1.5 × 2.4 mm 2 .

Fighting the Financial Crisis in Greece: The Privileged Company to Protect Production and Trade in Currants (1905) as International Bank Cooperation - Schönhärl, Korinna (The Historical Review/La Revue Historique)
The global economic crisis in the 1890s affected the economy of Greece severely, and in 1893 the Greek State had to stop servicing its foreign debt. Part of the problem was the lack of diversity of Greek agricultural production, which was focused on raisins and currants (especially flavourful raisins, grown exclusively in the area around Corinth) for export. The collapse of market prices for this good seriously affected the Greek treasury and society in the growing regions. The Greek government responded by trying to withhold part of the harvest in fertile years to stabilise world market prices. Plans to organise a monopoly company for the currant trade necessitated high sums of capital from abroad. This article investigates the question of how foreign bankers in London (Hambro & Son, Emile Erlanger) and Paris (Banque de l’Union Parisienne) could be convinced to participate in the project. Which factors allowed foreign bankers to trust in the Greek national economy despite its poor reputation? What factors influenced their risk management? The focus is on the role of Greek brokers in persuading the foreigners to invest in Greece, especially the role played by Ioannis Pesmazoglou, the director of the young and innovative Bank of Athens.
Keywords: History

122 GHz Patch Antenna Designs by Using BCB Above SiGe BiCMOS wafer process for system-on-chip applications - Wang, Ruoyu; Kaynak, Mehmet; Sun, Yaoming; Borngräber, Johannes; Beer, Stefan; Goettel, B.; Scheytt, Christoph (24th Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications)
Two half-wavelength 122 GHz patch antennas were designed and manufactured by using Benzocyclobutene (BCB) as a dielectric layer above the SiGe BiCMOS wafer. It enables the full integration of the millimeter-wave transceiver circuits and the antennas on a single chip to simplify the packaging procedure at millimeter-wave frequencies, thereby reducing the cost. The two patch antennas are fed by different feeding methods, i.e. microstrip transmission line direct feed and proximity-coupled feed. They exhibit similar performance and offer the flexibility of designing the interconnects (feed lines routing) between the circuits and the antennas within the very limited chip area. The measured gain is 3.4 dBi at 122.5 GHz (the center frequency of the ISM band of 122-123 GHz) for both designs with a simulated efficiency of about 50%.